Preoperative medication use and development of postoperative delirium and cognitive dysfunction - Maria Heinrich; Anja Nottbrock; Friedrich Borchers; Rudolf Mörgeli; Jochen Kruppa; Georg Winterer; Arjen J. C. Slooter; Claudia Spies; the BioCog Consortium (Wiley, 2021)
Abstract Postoperative delirium (POD) and postoperative (neuro‐)cognitive disorder (POCD) are frequent and serious complications after operations. We aim to investigate the association between pre‐operative polypharmacy and potentially inappropriate medications and the development of POD/POCD in elderly patients. This investigation is part of the European BioCog project (www.biocog.eu), a prospective multicenter observational study with elderly surgical patients. Patients with a Mini‐Mental State Examination score less than or equal to 23 points were excluded. POD was assessed up to 7 days after surgery using the Nursing Delirium Screening Scale, Confusion Assessment Method (for the intensive care unit [ICU]), and a patient chart review. POCD was assessed 3 months after surgery with a neuropsychological test battery. Pre‐operative long‐term medication was evaluated in terms of polypharmacy (≥5 agents) and potentially inappropriate medication (defined by the PRISCUS and European list of potentially inappropriate medications [EU(7)‐PIM] lists), and associations with POD and POCD were analyzed using logistic regression analysis. Eight hundred thirty‐seven participants were included for analysis of POD and 562 participants for POCD. Of these, 165 patients (19.7%) fulfilled the criteria of POD and 60 (10.7%) for POCD. After adjusting for confounders, pre‐operative polypharmacy and intake of potentially inappropriate medications could not be shown to be associated with the development of POD nor POCD. We found no associations between pre‐operative polypharmacy and potentially inappropriate medications and development of POD and POCD. Future studies should focus on the evaluation of drug interactions to determine whether patients benefit from a pre‐operative adjustment.